A prospective study on bacterial and atypical etiology of acute exacerbation in chronic obstructive pulmonary disease. (November 2014) - Nakou, Alexandra; Papaparaskevas, Joseph; Diamantea, Filia; Skarmoutsou, Nikoletta; Polychronopoulos, Vlasis; Tsakris, Athanassios
ABSTRACT : Aim: The bacterial and atypical etiology of acute exacerbations of chronic obstructive pulmonary disease was investigated and the diagnostic techniques used were compared among 92 hospitalized patients.Materials & methods: Sputum specimens were investigated using culture and PCR, serological status evaluation was performed and the inflammatory profile was associated with the microbiological results.Results & conclusion: The majority of the patients (65.2%) had very severe airway obstruction. The most common bacteria were Haemophilus influenzae and Pseudomonas aeruginosa (23.9 and 14.1%, respectively). Acinetobacter baumannii - and P. aeruginosa -positive cultures were associated with prolonged hospitalization and severe airway obstruction (p = 0.03 and 0.031, respectively). Chlamydia pneumoniae or Mycoplasma pneumoniae infection was diagnosed in four and two patients, respectively. Discrepant results were detected between PCR and serology, especially regarding C. pneumoniae .